Evaluating The Suitability of Sunflowers as Companion Plants in an Intercropping System with Tomatoes - Yuniati, Ratna; Karimah, Siti Zahrotul; Hemelda, Niarsi Merry (Malaysian Journal of Science (MJS), 2025)
The intercropping system involves growing multiple crop species simultaneously on the same land to reduce the risk of crop failure. One such example is the co-cultivation of sunflowers and tomatoes, where sunflowers function as living mulch. However, studies on the function and impact of sunflower–tomato intercropping systems, particularly in relation to weed management and productivity enhancement in Indonesia, remain limited. This study aims to evaluate the suitability of sunflower plants as companion and living mulch species in intercropping systems with tomatoes, and to assess the performance of both crops when grown individually or together. A randomized block design with two replications per treatment was employed using raised beds. Both crops were transplanted simultaneously in alternating arrangements for 13 weeks at a 1:1 ratio. Results showed that intercropping effectively suppressed weed growth and reduced pest and disease incidence. The Mann–Whitney test (P < 0.05) revealed significantly lower sunflower yields in the intercropping system than in monocropping. A Land Equivalent Ratio (LER) of 0.65 (<1) indicated higher productivity under monocropping, due to intense belowground interspecific competition and rhizosphere interactions. Competition analysis showed that tomatoes dominated the system (Aggressiveness, A = +0.165; Competition Ratio, CR = 1.677). Therefore, sunflower and tomato plants can be effectively intercropped, provided that planting times are staggered to minimize competition and aggressiveness between species.